Effects of different lubricants on bicycle chains: tribological and ecological study - Aubert, R.; Lallemand, F.; Grappe, F. (Journal of Science and Cycling, 2021)
Among the forces a cyclist has to overcome, chain drive frictions represent up to 3.9% of the losses in efficiency (Kyle 1986, Atkinson 2003). Lubrication seems to have an impact on these losses (Michelsen 2015), as better lubes can reduce frictions by 2.1%. Though, no study was made in real locomotion conditions. This study investigates the impact of different lubricants on chain`s friction forces measuring the power output in real locomotion conditions. The effect of three different lubricants on the coefficient of friction (Fc, dimensionless) and mechanical cost (Mc, J.m-1.kg-1) were tested using mechanical test and exercise performed with bicycle respectively. Differences between lubes were found in tribological study as some of them have a lower Fc than others. However, no differences were observed forthe on-field measurements between the lubricants. This means that the tribological tests do not reflect accurately what occurs in the bike transmission. In order to put a link between the very accurate measures of tribology and the less accurate measures performed on-field, a friction bench device should be envisaged.